Cover Image, Volume 5, Number 4, April 2023. Issue 4 (25th April 2023) - Wu, Anqi; Li, Chaolei; Han, Beibei; Liu, Wu; Zhang, Yang; Hanson, Svenja; Guan, Wanbing; Singhal, Subhash C.
Abstract : Front cover image : Solid oxide electrolytic cell (SOEC) is an efficient energy conversion device, which can transfer power to gas and realize energy storage. In article number: 10.1002/cey2.262, Wu et al. proposed the pulsed current strategy to replicate intermittent renewable energy, and investigated the stability and conversion rate of the flat‐tube SOEC under cyclic CO2 electrolysis operation, indicating the significant advantages of SOEC in efficient electrochemical energy conversion, carbon emission mitigation, and seasonal energy storage.